STEM DALAM PEMBELAJARAN IPA DI ERA REVOLUSI INDUSTRI 4. 0 - Suwito Singgih (Indonesian Journal of Natural Science Education, 2020)
The era of the industrial revolution 4.0 has an impact on science education to be able to prepare individuals who have competent competence in facing various challenges in the future, by applying technological advances in learning science. The STEM approach provides alternatives in science learning in an integrated manner with technology, engineering and mathematics. This study provides an overview of the role of STEM in learning science in the era of the industrial revolution 4.0. Based on the results of the research that was studied showed that STEM can direct the study of science closely related to technology, so that science has an important role in preparing superior human resources, both soft kill and hard skill. Science has a role in encouraging students to be able to apply their understanding of science in producing a work of technology that can be meaningful in everyday life. Through science learning, students can practice in developing their ability to think systematically, logically, and critically, so that it can be used to make discoveries and engineering by applying scientific steps.